THE SIMPLE MATHEMATICS OF VARIANCE ANALYSIS. - Kwang, Ching-Wen; Slavin, Albert (The Accounting Review, 1962)
The purpose of this article is to present the mathematical logic underlying variance computations. Variance analysis is often regarded by beginning students in cost accounting as one of the most difficult topics. They are confused by the intricate maze of alternative procedures and amounts used in variance computations and resort to memorizing the mechanics involved. Since in accounting a variance is always calculated as the difference between two related quantities, an understanding of the mathematical operations involved facilitates the understanding of the significance of the variance. A variance horn standard is defined as the difference between the standard cost and the actual cost incurred. The use of standard costs thus gives rise to variances between projected amounts and actual amounts for direct material and direct labor. Since price and quantity are the only variables present, the discussion that follows applies equally to either the analysis of direct material cost or of direct labor cost.